Minha escola, minha história - Lopes, Euzenir Pinheiro; Konrath, Joviane; Dias, Elorita Kátia Malvezzi; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf